Comparison of the efficacy and safety of neoadjuvant PD-1 inhibitors plus chemotherapy vs targeted therapy plus chemotherapy in locally advanced hypopharyngeal squamous cell carcinoma - Gao, Wen; Feng, Lifei; Zhao, Xinming; Huang, Zishi; Chen, Duoxuan; Yin, Gaofei; Guo, Wei; Zhong, Qi; Chen, Xiaohong; Fang, Jugao; Zhang, Yang; Huang, Zhigang (Frontiers in Immunology, 2024)
Objective: To investigate the clinical efficacy, preservation of laryngeal function, and safety differences between PD-1 inhibitors combined with chemotherapy, and targeted therapy combined with chemotherapy in LA HPSCC patients.This was a retrospective analysis of patients with LA HPSCC treated at Beijing Tongren Hospital, Capital Medical University from October, 2020 to March, 2024. A total of 110 eligible patients were included, 56 in the PD-1 inhibitors combined with chemotherapy group (Group A), and 54 in the targeted therapy combined with chemotherapy group (Group B). Relevant clinical data were collected, and the clinical efficacy, preservation of laryngeal function, complete response (CR) rate, pathological complete response (pCR) rate, major pathological response (MPR), and treatmentrelated adverse events (TRAEs) of the two groups were analyzed and compared.In both groups A and B, the objective response rate (ORR) and disease control rate (DCR) were similar with no significant differences, but the pCR rate in Group A was much higher than that in Group B, at 37.5% and 7.4%, respectively (p<0.001). The rate of primary tumor downstaging in group A was much higher than that in group B (76.8% vs. 38.9%) as well (p<0.0001). In addition, the 1y-OS rate in group A was 95.7%, compared to 87.0% in group B (p=0.106, HR=0.34; 95% CI: 0.114-1.013), and the 1y-PFS rate was 89.4% in group A compared to 85.2% in group B (p=0.399, HR=0.675; 95% CI: 0.275-1.659). Furthermore, the larynx function preservation rate was significantly higher in group A at 85.7%, compared to that of group B at only 66.7% (p=0.019). There were no deaths due to TRAEs in either group, and there was no significant difference in the incidence of grade 3-4 TRAEs between the two groups either (p=0.77). The main TRAEs in Group A were metabolism and nutrition disorders (52/56, 92.9%) and, in Group B were blood and lymphatic system disorders (40/54, 74.1%).PD-1 inhibitors combined with chemotherapy showed better short-term efficacy compared to targeted therapy. Additionally, a trend toward improved long-term survival was observed with PD-1 inhibitors but not with targeted therapy. Results for both groups indicate that neoadjuvant therapy is both safe and manageable.